Radiotherapy-induced abscopal effects in immune checkpoint inhibitor-refractory metastatic disease: results from a large multicenter real-world cohort study - Trommer, Maike; Rühle, Alexander; Lamrani, Allison; Frei, Charlotte; Kaufmann, Justus; Mäurer, Matthias; Wurschi, Georg; Jiang, Ping; Ehret, Felix; Baehr, Andrea; Hardt, Annika; Bodensohn, Raphael; et al. (OncoImmunology, 2026)
Combining radiotherapy with immune checkpoint inhibitors (RT-ICI) triggers systemic antitumor responses, such as abscopal effects (AbE). Predictors of AbE and its impact on survival in real-world settings remain poorly defined. This multicenter, retrospective cohort study assessed the prevalence of AbE in ICI-refractory progressive metastatic patients by evaluating the additive effect of RT on nonirradiated lesions (NIL). We screened 3773 cases to identify patients with stage IV tumors receiving RT during/after ICI. Abscopal benefit (AB) was defined as abscopal response (AR) or control (AC) by measuring NILs according to iRECIST. AB was observed in 61.3% of 142 included patients and associated with improved median overall survival (18 vs. 8 months, p < 0.01) and progression-free survival (7 vs. 3 months, p < 0.01). Logistic regression identified younger age (OR = 0.951, 95% CI: 0.903–0.995, p = 0.039) and longer ICI-RT intervals (OR = 1.077, 95% CI: 1.019–1.171, p = 0.027) as predictors of AB. There was no association between radiation dose or tumor volume and AB. Cox regression identified BMI ≥ 25 kg/m2 (HR = 3.348, 95% CI: 1.557–7.202, p = 0.002) and CRP ≥ 5 mg/l (HR = 3.058, 95% CI: 1.211–7.724, p = 0.016) as independent negative prognostic factors for survival in this RT-ICI cohort. Median survival was significantly higher among patients receiving ultrahypofractionated RT, compared to other fractions (21 vs. 11 months; p = 0.024). AbE seems to occur reliably and is prognostically relevant in ICI-refractory patients receiving RT. Patient- and timing-related factors were more predictive than RT details in our cohort. Our findings enhance the understanding of tailored RT-ICI approaches and lay the groundwork for targeted radioimmunotherapy strategies and personalized clinical trial designs.
CRIS-Team Scopus Importer:2026-01-23
Keywords: Abscopal effect; immune checkpoint inhibitor resistance; immunotherapy; metastatic cancer; radiotherapy